Pomen Dragotina Cvetka za razvoj slovenskega glasbenega zgodovinopisja - Barbo, Matjaž (De musica disserenda, 2012)
The paper presents Dragotin Cvetko's work with a special emphasis on his setting up institutional foundations for the development of musicology in Slovenia, which he understood, first and foremost, as a historiographical discipline with a specific national status. Cvetko's musicological legacy gained considerable international acclaim and has remained indispensable for further development of Slovenian musicology.
Keywords: Cvetko, Dragotin, 1911-1993; zgodovina glasbe; glasbene študije; glasba; music; muzikologija; history; zgodovinopisje; Slovenia; Slovenija